Desarrollo e implementación de una máquina (CNC) para la gestión automática de cultivo y riego de un huerto dentro de un hogar basado en la propuesta de Farmbot - Sánchez Morales, Edier Alexander (Universidad Antonio Nariño, 2023)
The current degree document is proposed the construction of a cartesian-type CNC machine that has movement in the X, Y and Z axes based on the Farmbot robot, which seeks to carry out the automatic management of tasks such as irrigation and plant cultivation, this is based on the constant search for new models in urban agriculture that expose better efficiency in the area of cultivation, control, production and considers itself as an alternative accordingly to the decrease in arable land due to the difference in agricultural areas that have been converted into residential, urban and and/or industrial growth areas.